Biological variation in musculoskeletal injuries: current knowledge, future research and practical implications. Issue 23 (26th October 2015) - Collins, Malcolm; September, Alison V; Posthumus, Michael
Abstract : Evidence from familial and genetic association studies have reported that DNA sequence variants play an important role, together with non-genetic factors, in the aetiology of both exercise-associated and occupational-associated acute and chronic musculoskeletal soft tissue injuries. The associated variants, which have been identified to date, may contribute to the interindividual variation in the structure and, by implication, mechanical properties of the collagen fibril and surrounding matrix within musculoskeletal soft tissues, as well as their response to mechanical loading and other stimuli. Future work should focus on the establishment of multidisciplinary international consortia for the identification of biologically relevant variants involved in modulating injury risk. These consortia will improve the limitations of the published hypothesis-driven genetic association studies, since they will allow resources to be pooled in recruiting large well-characterised cohorts required for whole-genome screening. Finally, clinicians and coaches need to be aware that many direct-to-consumer companies are currently marketing genetic tests directly to athletes without it being requested by an appropriately qualified healthcare professional, and without interpretation alongside other clinical indicators or lifestyle factors. These specific genetic tests are premature and are not necessarily required to evaluate susceptibility to musculoskeletal soft tissue injury. Current practice should rather consider susceptibility through known risk factors such as a positive family history of a specific injury, a history of other tendon and/or ligament injuries and participation in activities associated with the specific musculoskeletal injuries. Potential susceptible athletes may then be individually managed to reduce their risk profile.